Coagulopathy parameters in symptomatic and asymptomatic Pregnant Women with COVID-19 - Pelin, Ana-Maria; Maftei, Nicoleta Maricica; Georgescu, Costinela; Roşca, Ștefan; Roşca, Ramona Oana; Pelin, Ioana; Ștefanescu, Cristina (Technium BioChemMed, 2024)
Abstract: Purpose: The purpose of the study was to determine if the physiological hypercoagulability during pregnancy is compounded by SARS-CoV-2 infection-induced coagulability. Patients and methods: We retrospectively analysed (October 2020 and August 2021) modifications of the coagulation parameters recommended by the ISTH (International Society on Thrombosis and Haemostasis) (fibrinogen, APTT, PT, INR, D-dimers complete blood count) in 96 pregnant women infected with SARS-CoV-2. Results: Our results indicated that none patients had severe evolution of the SARS-CoV-2 infection and did not require transfer to the ICU. We also monitored the variation of such parameters, depending on subsequent SARS-CoV-2 PCR screening tests. We established that the laboratory parameters used to assess the coagulability are directly correlated with positive SARS-CoV-2 tests, and pregnancy represents a condition that is likely to increase the risk of embolisms in pregnant patients infected with SARS-CoV-2, compared with the general population. No cases of confirmed SARS-CoV-2 infection were observed in the neonates. Conclusion: Knowledge of laboratory modifications with prognostic utility in relation to coagulation may be extremely valuable in the management of pregnant women with COVID-19. A better understanding of coagulopathy caused by COVID-19 would also be helpful to guide treatment recommendations for pregnant women. Pregnancy may also be an additional risk factor for coagulopathy in women infected with SARS-CoV-2 in both symptomatic and asymptomatic positive pregnant women.